2022
DOI: 10.1186/s12917-022-03171-1
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of neuropathogenic equid herpesvirus 1 causing abortions in Yili horses of Zhaosu, North Xinjiang, China

Abstract: Background EHV-1 is one of the most serious viral pathogens that frequently cause abortion in horses around the world. However, so far, relatively little information is available on EHV-1 infections as they occur in China. In January 2021, during an abortion storm which occurred in Yili horses at the Chinese State Studs of Zhaosu (North Xinjiang, China), 43 out of 800 pregnant mares aborted. Results PCR detection revealed the presence of EHV-1 in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Despite the availability of vaccines and the implementation of good husbandry conditions, EHV1 continues to be one of the most commonly reported causes of equine abortion worldwide. 7,14,15,18,26 In our study, information about the vaccination status of the dam was not available in most cases.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the availability of vaccines and the implementation of good husbandry conditions, EHV1 continues to be one of the most commonly reported causes of equine abortion worldwide. 7,14,15,18,26 In our study, information about the vaccination status of the dam was not available in most cases.…”
Section: Discussionmentioning
confidence: 97%
“…however, in our country, only four papers published in 2016, and 2022 showed that EHV-1 had been found in aborted fetal lung tissue of mares. Of these studies, three researches revealed that EHV-1 was responsible for abortion of Yili horses from the Chinese State Studs in Zhaosu county, 2015 [5], and 2021 [7,16], respectively.one research reported that the virus was detected in aborted samples of Przewalski's horse conservation center in Jimusaer county, 2019 [17]. until now, there is no information on EHV-1 involving in respiratory problem of horses, China.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of EHV-1 DNA in these nucleic acid samples was subsequently detected by TaqMan-MGB qPCR by targeting partial ORF68 genes, primers and probe in Table S1. For the qPCR, SuperReal PreMix (Tiangen Biotech Co.) was used to amplify the target genes under the following conditions: an initial denaturation at 95°C for 15 min, followed by 45 cycles, each with a denaturation step at 94°C 30 s, an annealing and an extension steps at 60°C 30 s. EHV-2 (716 nt), EHV-4 (587 nt) and EHV-5 (881 nt) DNA in these nucleic acid samples was subsequently detected by PCR by targeting partial ORF33 (EHV-4) or ORF8 (EHV-5 or EHV-2) genes (encoding the gB) as previous published studies [7,16,24].…”
Section: Dna Extraction and Ehvs Detectionmentioning
confidence: 99%
See 2 more Smart Citations